(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Preterm infants are at risk for long term neurodevelopmental impairements. Neurodevelopmental assessment at early months of infancy has been proposed as a valuable tool for prediction of neurodevelopmental outcomes in this population. Objective: The present study attempted to find the neurodevelopmental impairments in preterm infants and thus to identify the at risk infants for follow up and subsequent therapeutic intervention. Methodology: This prospective cross-sectional observational study was conducted in Dhaka Shishu (Children) Hospital from October 2011 to March, 2012. A total 103 preterm neonates who met the inclusion criteria underwent rapid neurodevelopmental assessment (RNDA) at neonatal period and again at their 3 months of age to find the at risk infants for long term neurodevelopmental impairments. Results: Among the enrolled 103 preterm infants during RNDA at neonatal period, abnormal domains found in primitive reflexes 41(39.7%), gross motor 42(40.7%), fine motor 32(31%), vision 40(38.7%), hearing 32 (31%), speech 40(38.7%), cognition 3(2.8%), behavior 3 (2.8%) and 3(2.8%) had seizure. Again in RNDA at 3 months of age, the no. of preterm infants having abnormal developmental domains are: gross motor 49(47.5%), fine motor 19(18.3), vision 9(8.6%), hearing 16(15.4%), speech 15 (14.5%), cognition 6(5.7%), speech 15 (14.5%), cognition 6(5.7%), behavior 11(10.6%) and 3 (2.9%) had seizure. Conclusion: The identification of neurodevelopmental impairments in early months of preterm infants should offer a valuable complement to tools for identification of at risk infants for long term sequlae (in neurodevelopmental impairment). Bangladesh J Child Health 2016; VOL 40 (1) :5-11